Residual trees response to selective cutting operations in Caspian forests - Behjou, Farshad Keivan (Array, 2020)
Damages to residual trees caused by felling operation were assessed in the stands of a Caspian hardwood forest. Following the felling operation, a field survey was done to collect data of all residual trees (species, DBH, height) and of tree wounds (size class, location, intensity of damage). Different harvesting intensities were studied, and treatments were replicated three times. The results showed that the treatment with the medium and high harvest intensity was found to cause the highest percentage of damage and the largest stem wounds. It is concluded that harvesting intensity should be limited to 3 trees/ha during each harvesting operation to reduce the extent of tree damage and thus future financial loss.